2003
DOI: 10.1002/jssc.200390067
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the use of microemulsions as eluents in high‐performance liquid chromatography

Abstract: Evaluation of the use of microemulsions as eluents in high-performance liquid chromatographyAn overview of the use of microemulsions as eluents in HPLC is given. The separation mechanisms involved are discussed and the technique is compared to solvent modified micellar chromatography as well as to ordinary reversed-phase HPLC in order to evaluate differences and similarities. The microemulsion systems have been used for the separation of a number of antihypertensives and non steroidal antiinflammatory drug sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 17 publications
1
25
0
1
Order By: Relevance
“…Water-soluble analytes will reside mainly in the aqueous phase and their retention is largely controlled by stationary phase interactions. The hydrophobic organic solvents used to create the droplets are also distributed to some extent on the surface of the column, which increases the amount of stationary phase and also affects solute selectivity and retention [8]. Together, all of these partitioning mechanisms control the retention and separation of solutes in an MELC separation.…”
Section: Background To O/w and W/o Melcmentioning
confidence: 99%
“…Water-soluble analytes will reside mainly in the aqueous phase and their retention is largely controlled by stationary phase interactions. The hydrophobic organic solvents used to create the droplets are also distributed to some extent on the surface of the column, which increases the amount of stationary phase and also affects solute selectivity and retention [8]. Together, all of these partitioning mechanisms control the retention and separation of solutes in an MELC separation.…”
Section: Background To O/w and W/o Melcmentioning
confidence: 99%
“…However, hydrophobic organic solvents that represent the internal phase of microemulsion eluent, as well as the molecules of surfactant, may bind to the stationary phase and therefore induce the significant changes of its characteristics. 1 That is why the prediction of retention behavior may be more complicated.…”
Section: Microemulsions As Eluents In Liquid Chromatographymentioning
confidence: 99%
“…For example, in 1986, Dorsey and coworkers [11] first reported the feasibility of using w/o microemulsions as mobile phases in normal-phase HPLC, in which water molecules were trapped into reversed micelles and thus the deleterious effect of water molecules on the silica stationary phases was greatly reduced, but efficiency of separation was found to be very poor in general. More recently, Hansen and coworkers [12] demonstrated that comparable separation efficiencies to conventional HPLC can be achieved when using o/w microemulsions as mobile phases in RP HPLC. Advantages included much shorter retention times obtainable for lipophilic substances (thus avoiding the need of gradient elution), simpler sample preparation of lipophilic samples due to enhanced solubilization capacity of microemulsion solvents, as well as possible direct sample injection of biofluids.…”
Section: Introductionmentioning
confidence: 99%